(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The article highlights the peculiarities of preschool education in the countries of the Near East, especially Singapore. It talks about the personnel training system for preschool education, the uniqueness of education in the preschool education system, the existence of alternative and partner organizations dealing with preschool education problems in the country.